2015
DOI: 10.7863/ultra.34.4.679
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Color Doppler Sonography for Evaluating Relative Displacement Between the Flexor Tendon and Subsynovial Connective Tissue

Abstract: We demonstrated the validity of color Doppler displacement for use in the evaluation of relative motion. Color Doppler sonography is useful in our understanding of the behavior of the subsynovial connective tissue during tendon excursion, which may elucidate the role of finger motion in the etiology of shear injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
32
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 25 publications
3
32
1
Order By: Relevance
“…Full finger F/E produced the lowest MVR of 64.5% ± 2.9% while PIP + DIP joint F/E generated the highest at 68.4% ± 2.6%. This trend is consistent with cadaver studies that showed prescribed tendon velocity increased relative motion between the FDS tendon and SSCT . Although, participants self‐selected their movement pace, the finger movements produced fairly low FDS tendon velocities (<59.6 ± 3.3 mm/s), thus minimizing the viscous effects of the paratenon in our study.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Full finger F/E produced the lowest MVR of 64.5% ± 2.9% while PIP + DIP joint F/E generated the highest at 68.4% ± 2.6%. This trend is consistent with cadaver studies that showed prescribed tendon velocity increased relative motion between the FDS tendon and SSCT . Although, participants self‐selected their movement pace, the finger movements produced fairly low FDS tendon velocities (<59.6 ± 3.3 mm/s), thus minimizing the viscous effects of the paratenon in our study.…”
Section: Discussionsupporting
confidence: 90%
“…However, we also found a significant 5.7% decrease in relative displacement from 0° to 30° wrist extension while Yoshii and colleagues found similar relative displacements for 0°, 30°, and 60° wrist extension. Testing the effect of wrist posture on relative motion in a cadaveric model is particularly challenging since the flexor tendons are detached from the proximal and distal attachment sites . Strain‐related changes of the SSCT during wrist motion influence its viscoelastic properties, which in turn affect relative motion between FDS tendon and SSCT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations